Gestión del talento humano para la empresa direl franquiciado Disensa de la ciudad de Loja. - Rengel Ojeda, Miguel Alejandro (2012)
This research work was carried out in the Company DIREL franchisee dissent from the City of Loja is located on University Avenue street 03 to 52 and Quito against Isidro Ayora Hospital. In order to highlight the problems related to the topic Human Resource Management in Business "Franchisee DIREL dissent" from the city of Loja, we proceeded to collect the information through the implementation of employee surveys and an interview with manager, whose information permitted to know the reality of the same relation to the management of human talent. It is hereby constituted a literature review using concepts and content related to the topic, the same that allows an understanding of the importance of human talent within a company also worth stressing that the issue is identified with the traditional school or scientific and that is developed through observation and systematic study of the facts, become a basis on which studies can build and improve society. In the results took into consideration the information obtained from surveys of staff of the company "Franchisee DIREL dissent" from the city of Loja and interview the manager, whose information allowed to know how the company is organized; questions the survey and interviews were analyzed and plotted, which yielded the following results: Of the 20 employees surveyed who correspond to 100%, we see that the distributor has 7 people DIREL female equivalent to 35% and 65% male, giving a total of 13, 60% of employees the company have 20 to 30 years, 20% from 31 to 40 years, 10% from 41 to 50 years and finally 10% have from 51 to 60 years' salaries by 50% is between 301 and $ 500, 100 to $ 300 25% 501 to $ 700 25% $ 701 and onwards to 10%, 30% of staff are graduates of a university, 25% bachelors, 15 % Commercial Engineer, also the 15% have completed the basic cycle and 5% in Finance Ing, 45% of employees are working within the company from one to three years, 25% from 4 to 10 years , 20% of one month to eleven months and 10% from eleven to fifteen years, we see that 2 people, or 10% think that the initiative in their work required is to have good communication with the to grab new customers and gain greater acceptance in the market, a person with 5%, shows us that change is to be a good leader, three people which equates to 15% indicate that it functions to develop them entrusted, and also have the patience to know the market and also to work under pressure, while 4 employees with 20% more each told us is to persevere and have knowledge of the market, of the 20 respondents sixteen corresponding to 80% in the company believe that if done recruiting, and four corresponding to 20% did not apply any kind of recruitment in the company, the selection process in the company led DIREL of According to the respondents is given by the presentation of the resume with 85% and interviews with 15%, not considering, testing, research and medical evaluation conducted by the hiring company can say that it makes the vast part by the granting of a contract year and then its subsequent renovation with 65% of respondents, while 25% had a probationary contract, and 10% have an indefinite contract, 90% of respondents do not know the existence of a welcoming hand to inform policy and other general corporate information, while 10% state that if there is a welcome manual, 40% of the respondents stated that if there is training as that 60% think that training is not performed and training within the company, 25% of respondents were motivated by the company, while the remaining 75% can not receive any reasons, 90% of respondents state that the company has not conducted a job evaluation while the remaining 10% indicate that if there has been a job evaluation. Raised in the discussion of the results the same as a proposal is to improve the organization of human talent in the company, developing models of recruitment, selection, hiring, induction, training and motivation, job evaluation of each employee the company "Franchisee DIREL dissent" from the city of Loja. Was reached the following conclusions: Not fully implemented in stages of recruitment, selection and recruitment, induction, likewise there is no adequate trained staff, the company does not have a process of work motivation, where the stimulation staff have a better way to perform their functions do not have a welcome manual which clearly specify the policies, obligations, duties and rights as employees and employer and has not been made and no job evaluation to enable them to know if your professional or academic training is in line with the roles within the company, plus if the remuneration received is subject to their work. Under these findings we propose the following recommendations: That consideration be given to the proposals and implement them in order to have a proper process of recruitment, selection, hiring, induction and training, the plan is implemented Motivation raised to staff; welcome manual which clearly states the mission, vision, policies, regulations, duties and rights of both employees and the employer's job evaluation used, so this way there is an equitable distribution of wages for employees who are part of this company. The bibliography contains bibliographic sources from which information has been extracted over the investigation. Finally, we present the annexes containing all the documents that supported the development of this work, as the survey format for the staff and the format of the interview the manager.